4‐3: Distinguished Paper: 10 µm Pixel, Quantum‐dots Color Conversion Layer for High Resolution and Full Color Active Matrix Micro‐LED Display. Issue 1 (29th May 2019) - Kim, Hyo-Min; Ryu, Misun; Cha, James H.J.; Kim, Hyun Soo; Jeong, Tak; Jang, Jin
Abstract : A fine patternable quantum‐dots (QDs) color conversion layer (CCL) for high resolution and full color active matrix (AM) micro‐LED display is demonstrated. QDs CCL could be patterned until 10 µm using photolithography process. It is found that multi‐coatings with R‐ and G‐QD CCLs on LED array can provide full color AM display.